Regulation of Cellular Processes by Interleukin‐16 in Homeostasis and Cancer. Issue 2 (25th October 2013) - Richmond, Jillian; Tuzova, Marina; Cruikshank, William; Center, David
Abstract Interleukin‐16 (IL‐16) is generated as a precursor molecule that is cleaved by caspase‐3 to produce a pro‐IL‐16 molecule that functions as a regulator of T cell growth, and a secreted peptide that functions as a CD4 and/or CD9 ligand for induction of cell motility and activation. IL‐16 has been predominantly studied as a contributing factor in the orchestration of an immune response; however, more recently IL‐16 bioactivity has been closely associated with the progression of a number of different cancers. While the association between IL‐16 plasma levels and tumor progression has been reported for many types of cancer, the mechanism for IL‐16 involvement has been partially elucidated for three of the cancer types, cutaneous T cell lymphoma (CTCL), multiple myeloma (MM), and breast cancer. The mechanism for promoting cell growth is different in each of these cancers and involves a sequence mutation in the pro‐molecule facilitating decreased p27KIP1 levels in CTCL; over expression of the secreted IL‐16 molecule to induce proliferation in CTCL T cells, and plasma cells in MM; and increased secreted IL‐16 acting to recruit CD4+ pro‐tumor macrophages in breast cancer. This article will review the cellular process for generating IL‐16, the biological activities for both the pro‐ and secreted forms of the protein, and then the mechanism by which these forms contribute to cancer progression. As a soluble cytokine the ability to reduce or eliminate IL‐16 synthesis through siRNA approaches or bioactivity through the use of neutralizing antibody treatment may represent a novel therapeutic approach. J. Cell. Physiol. 229: 139–147, 2014. © 2013 Wiley Periodicals, Inc.